Surgical approaches to the cervical lymph nodes in the treatment of oralsquamous cell carcinomas - Davudov, mahammad (Journal of Medical Biomedical and Applied Sciences, 2019)
Introduction:About 90 per cent of all malignant tumors of head and neck area fall on the “squamous cell carcinoma” of mucous and skin coverings of that area,  having the high probability of regional metastasis. When using the surgery for such pathology the selection of intervention method on regional lymphatic apparatus is still negotiable. Material and methods: 35 patients with the various types of neck dissection have been examined. The efficiency of the methods was assessed base on the clinical and radiologic indicators. Results: it was revealed that functional  neck dissection is the most optimal one during the malignant diseases in the oral cavity and the maxillofacial area.   Conclusion: According to our research work functional dissection of neck lymph nodes are recommended in case of patients with cN0.This will help to have a better post operation treatment for patients.